2017
DOI: 10.1007/s40615-017-0404-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Cervical Cancer Screening Among Hispanic Immigrant Women in Coastal South Carolina

Abstract: Differences in cervical cancer screening for participants were partially explained by psychosocial factors, health status, and individual and structural barriers to healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…major barriers to cervical cancer screening [14,15,22,37,38]. Our findings are consistent with results of a previous study using MBMT-3 data, which found that 72% of participants perceived financial barriers to screening and that uninsured women were more likely to perceive screening costs and follow-up treatment costs as barriers [39].…”
Section: Plos Onesupporting
confidence: 90%
“…major barriers to cervical cancer screening [14,15,22,37,38]. Our findings are consistent with results of a previous study using MBMT-3 data, which found that 72% of participants perceived financial barriers to screening and that uninsured women were more likely to perceive screening costs and follow-up treatment costs as barriers [39].…”
Section: Plos Onesupporting
confidence: 90%
“…Studies have found that reports of chronic illnesses, such as hypertension, diabetes, and obesity, have a negative relationship with being up-to-date with cervical cancer screening among women in general [ 35 37 ], including immigrant women [ 38 ]. In contrast to earlier studies, our study found a positive relationship between having one or more chronic illnesses and cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Public awareness of the dangers of SHS exposure should be enhanced. In addition, it is necessary that cervical screening should be performed for married women every 3 to 5 years, depending on age and screening modality (Pap test only or combined with the HPV-DNA test, referred to as ‘co-testing’ ) 35 , in order to diagnose and intervene early, and to reduce the incidence and mortality of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%